2022
DOI: 10.1371/journal.pone.0263931
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle changes in patients with non-alcoholic fatty liver disease: A systematic review and meta-analysis

Abstract: Background Non-alcoholic fatty liver disease is a liver condition that is increasing worldwide and expected to become the number one cause of cirrhosis and hepatocellular carcinoma in the next 5 years. Currently there are no successful or approved pharmacological treatments. Weight loss is the first-line therapy as a 7 to 10% reduction improves steatosis, inflammation, hepatocyte ballooning, and fibrosis. To achieve this, lifestyle interventions including daily exercise and diet must be encouraged. We aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 93 publications
(124 reference statements)
0
60
0
Order By: Relevance
“…In NAFLD treatment, exercise is recommended by clinicalpractice guidelines. 13,15 The recommendations are established upon the findings that exercise overall, without weight loss, produces a 20%-30% relative reduction in hepatic fat content, 128,129 with similar effects of different modalities of exercise (aerobic exercise, resistance exercise, or high-intensity intermittent exercise).…”
Section: -4 Veg Unitsmentioning
confidence: 99%
See 3 more Smart Citations
“…In NAFLD treatment, exercise is recommended by clinicalpractice guidelines. 13,15 The recommendations are established upon the findings that exercise overall, without weight loss, produces a 20%-30% relative reduction in hepatic fat content, 128,129 with similar effects of different modalities of exercise (aerobic exercise, resistance exercise, or high-intensity intermittent exercise).…”
Section: -4 Veg Unitsmentioning
confidence: 99%
“…130 A recent meta-analysis using 16 RCTs of exercise intervention showed that exercise significantly reduced liver fat compared to the control group. 129 Studies reporting the effects of exercise in people with fibrosis are limited. A 12-week aerobic exercise non-controlled intervention led to reduced fibrosis by one stage, according to repeated liver biopsy, in about 60% of patients.…”
Section: -4 Veg Unitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the findings presented here strongly indicate that the anti-steatotic and hepatoprotective effects against lipotoxicity exerted by CA are absolutely dependent upon AhR-mediated Stc2 signaling. (Fernández et al, 2022).…”
Section: Ca Regulates Lipid Metabolism In Vivomentioning
confidence: 99%